Effect of the Intravaginal Inoculation of Phytobiotics in a Murine Experimental Model (Global Journal of Medical Research, 2024)
Lactobacilli play a fundamental role in maintaining health and preventing infections of the female urogenital tract Complementary use of vegetal extracts selected for their ethnopharmacological characteristics and conventional uses for the different conditions in the human body as an adequate alternative therapy for the restoration of the vaginal microbiome has emerged Compatibility of phytoextracts with lactobacilli for the design of phytobiotic formulas was determined previously Safety of selected combinations by the intravaginal i va administration in a murine model was evaluated to determine if some type of adverse effect was produced in the host Lactobacillus gasseri CRL1320 Limosilactobacillus reuteri CRL1324 Ligilactobacillus salivarius CRL1328 and Lacticaseibacillus rhamnosus CRL1332 combined with Hamamelis-virginiana Amaranthus-muricatus and Smilax- spera were inoculated individually or combined in mice vagina 7 daily doses
Keywords: beneficial lactobacilli; vegetal-extracts; phytobiotics; safety; vaginal murine; adverse effect